Why buy American'' is a bad idea but politicians still like it - Mario Larch; Wolfgang Lechthaler (Kiel Institute for the World Economy (IfW), 2009)
When the world economy was recently hit by a severe recession, governments all over the world reacted by initiating stimulus packages. Some countries (among them, most notably, China and the US) tried to put special emphasis on their home industries by including Buy local'' clauses into the stimulus package. By analyzing the dynamics of transitory changes of trade barriers as a short-run response to an economic downturn, we show that beggar-thy-neighbor policy does not work. We then come up with two rationales that help to understand why countries nevertheless consider protectionism to be a good response to a recession: (i) the relationship between vulnerability and the degree of openness to trading partner countries, and (ii) the lobbying of domestic, non-exporting firms.
Keywords: F11; F12; F16; 330; Protectionism; trade liberalization; short term shocks; Antizyklische Finanzpolitik; Protektionismus; Herkunftsbezeichnung; Offene Volkswirtschaft; Schock; Spillover-Effekt; Interessenpolitik; Theorie